PREVALENCE AND MOLECULAR CHARACTERIZATION OF GLUCOSE-6-PHOSPHATE DEHYDROGENASE (G6PD) DEFICIENCY IN FEMALES FROM PREVIOUSLY MALARIA ENDEMIC REGIONS IN NORTHEASTERN THAILAND AND IDENTIFICATION OF A NOVEL G6PD VARIANT - Sumalai Dechyotin; Kittipong Sakunthai; Noppmats Khemtonglang; Supawadee Yamsri; Kanokwan Sanchaisuriya; Kriengkrai Kitcharoen; Suttiphan Kitcharoen (Mediterranean Journal of Hematology and Infectious Diseases, 2021)
Introduction: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common X-linked enzymopathy, highly prevalent in areas where malaria is or has been endemic. Prevalence of G6PD deficiency and characterization of G6PD variants in females from previously malaria endemic areas of northeast Thailand remain unstudied.